1995
DOI: 10.1111/j.1472-8206.1995.tb00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring and cardiovascular function tests in multiple system atrophy

Abstract: Cardiovascular tests (CT) of autonomic function and non-invasive ambulatory blood pressure (BP) and heart rate (HR) monitoring were performed in 17 patients with multiple system atrophy (MSA) (mean age 61 +/- 9 years) and in 12 healthy subjects matched for sex and age. CT showed severe autonomic dysfunction with orthostatic hypertension (OH) in eight patients with MSA (47%) (Group I). The remaining nine out of the 17 patients didn't show BP abnormalities during CT but an impaired HR reflex response was found (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Others have already reported abnormal 24‐hour BP profiles in a similar percentage of PD and MSA, but not PSP patients. Plaschke et al, Frongillo et al, and Brevetti et al described abnormalities of BP profiles in smaller cohorts of PD and MSA patients 17–19. Senard et al were able to demonstrate that PD patients with orthostatic hypotension presented with higher nocturnal BP values which is in line with our findings 20.…”
Section: Discussionsupporting
confidence: 91%
“…Others have already reported abnormal 24‐hour BP profiles in a similar percentage of PD and MSA, but not PSP patients. Plaschke et al, Frongillo et al, and Brevetti et al described abnormalities of BP profiles in smaller cohorts of PD and MSA patients 17–19. Senard et al were able to demonstrate that PD patients with orthostatic hypotension presented with higher nocturnal BP values which is in line with our findings 20.…”
Section: Discussionsupporting
confidence: 91%
“…OH has been reported in up to 50% of DLB patients , but only 21% of patients in stage 3 of the Hoehn and Yahr scale refer to postural symptoms . Finally, symptoms of OH are found in almost 50% of MSA patients, already in the early stages of the disease , with peak cross‐sectional prevalence of 75% and 81% in European and American cohorts . Nevertheless, patients with a long‐term history of OH may undergo compensatory changes that ensure adequate cerebral perfusion even in the case of severe OH .…”
Section: Orthostatic Hypotensionmentioning
confidence: 99%
“…In dysautonomic patients, impairment of sympathetic output and consequent failure of activating counterbalance mechanisms [31] also produce PPH, which is commonly defined as a decrease in SBP 20 mmHg within 2 h after a meal [32]. Preliminary cross-sectional studies reported PPH in 48% of dysautonomic PD patients [33] and 47% of MSA patients [24]. Although PPH was associated with instrumental evidence of OH and NH in both cases, the small sample size may have created a bias in these studies.…”
Section: Other Symptoms Of Cardiovascular Autonomic Failurementioning
confidence: 99%
“…The method is also suitable in evaluation of orthostatic hypotension featuring hypotensive episodes in conjunction with standing, post‐prandial hypotension and reversal of the normal decline in blood pressure at night (8). It has previously been used in this connection in PD (9, 10) and multiple system atrophy (11).…”
mentioning
confidence: 99%